The effect of owner versus management control on the choice of accounting method - Sia, Lay Yee (2014)
This project examines the relationship between the ownership control status of firms and the accounting methods they adopt. The arguments of Watts and Zimmerman's positive theory are integrated with those of managerial economists to generate the prediction that management-controlled firms are more likely than owner-controlled firms to adopt accounting methods which increase reported earnings. The alternative view is the Fama thesis that the managerial labour market acts as sufficient disciplining mechanism, such that there are no differences in the accounting procedures used in different ownership structures. The project compares the useful life of depreciable assets used by a sample of management- and owner-controlled firms for financial reporting purposes. The comparison considers and controls for the factors of firm size and leverage. The comparison reveals that there is no significant difference in the useful life of depreciable assets adopted by management-controlled and owner-controlled firms.